Predictive modelling of stock index by means of data mining techniques - Foong, Kar Seng (2008)
This study examines the value of technical, financial and macroeconomic variables in stock index prediction. In tandem, it also assesses the applicability of multiple regression and two data mining techniques: decision trees and artificial neural networks to develop prediction models for the purpose of forecasting the stock index.